Efektivitas Penegakan Hukum terhadap Judi Online di Indonesia: Analisis Yuridis dan Sosiologis - Juhara, Nasisca Fitria; Amalia, Mia; Mulyana, Aji (Journal of Contemporary Law Studies, 2025)
Online gambling is a phenomenon that is increasingly widespread in Indonesia and has significant social and economic impacts. This research aims to analyse the effectiveness of law enforcement against online gambling practices based on juridical and sociological perspectives. The method used is a normative juridical approach by analysing the applicable laws and regulations, such as the Criminal Code, ITE Law, and government policies in dealing with online gambling. Data was collected through literature study and interviews with law enforcement officials and cyber law experts. The results show that although the existing regulations are quite comprehensive, their implementation still faces obstacles, such as the lack of coordination between law enforcement agencies, technological limitations in detecting and blocking online gambling sites, and weak enforcement of sanctions against perpetrators. From a sociological perspective, the high rate of community participation in online gambling is influenced by economic factors and low digital literacy. In conclusion, a more effective strategy is needed to tackle online gambling, including strengthening regulations, increasing the capacity of law enforcement officials, and educating the public to raise awareness of the dangers of online gambling.